Duty Factor Is a Viable Measure to Classify Spontaneous Running Forms; Sports; Vol. 7, Iss. 11 - Patoz A. Aurelien; Gindre C. Cyrille; Thouvenot A. Adrien; Mourot L. Laurent; Hebert-Losier K. Kim; Lussiana T. Thibault (2019, 2019)
Title screen